Analyzing the Role of Transcutaneous Electrical Nerve Stimulation in Sports: A Literature Perspective on Its Application and Benefits in Physiotherapy - Jennifer Astra; Gusril Gusril; Bafirman Bafirman; Donal Syafrianto; Yovhandra Ockta; Firunika Intan Cahyani (Jurnal Penelitian Pendidikan IPA, 2024)
This study evaluates the application of Transcutaneous Electrical Nerve Stimulation (TENS) in sports physiotherapy, focusing on pain management, muscle recovery, and injury rehabilitation. Utilizing qualitative descriptive research based on a literature review, data were sourced from reputable scientific databases such as Scopus, ScienceDirect, and Google Scholar. The analysis revealed that TENS effectively manages pain by altering pain signals before they reach the brain, enhances muscle recovery by improving blood circulation, reducing inflammation, and accelerating healing. Additionally, TENS supports injury rehabilitation by preserving strength and muscle mass during immobilization and contributes positively to athletes' mental well-being by maintaining motivation. While TENS demonstrates various benefits, its effectiveness can vary among individuals, indicating a need for further research to optimize usage protocols and assess its impact on specific conditions in sports. In conclusion, TENS is a valuable tool in sports physiotherapy, offering significant advantages in pain relief, muscle recovery, and rehabilitation